Bridging Epistemology, SLA, and Cultural Content in BIPA Enhancing Indonesian Language Learning for Foreign Speakers - Tantri, Niki Raga; Fitrah, Yundi; Kusmana, Ade; Wulandari, Bunga Ayu; Utama, Galuh Tulus (Allure Journal, 2025)
This study investigates the epistemological foundations and Second Language Acquisition (SLA) principles underpinning the teaching and learning of Indonesian for foreign speakers (BIPA). Using a systematic literature review (SLR) approach, this research analyzed 16 studies on BIPA instructions published between 2020 and 2024 involving the identification of inclusion and exclusion criteria relevance to epistemology, SLA theories, and BIPA teaching. The methodology approach followed SLR guidelines by Evans Pearson (2001) including database searching employing Scopus or Google Scholar, and critically evaluated the chosen studies. To be in line with the theoretical frameworks and practical teaching strategies, data extraction placed a focus on epistemological methods and SLA issues. The results indicate that BIPA instructions in the selected articles align with the epistemology methods of empiricism, rationalism, constructivism, pragmatism, and hermeneutic, supporting SLA principles, such as language environment, comprehensible input, the roles of the first or second language, internal processing, and individual learner differences. Crucially, the study showed the other significant aspect that mostly in the selected articles yielded the importance of including Indonesian cultures in the teaching and learning BIPA process. This study improves BIPA instruction field by highlighting cultural literacy as fundamental in BIPA teaching and suggests its involvement as a learning strategy for language acquisition.